Analysis of SAT Type Foot-And-Mouth Disease Virus Capsid Proteins and the Identification of Putative Amino Acid Residues Affecting Virus Stability - Maree, Francois F. (Public Library of Science, 2013)
Foot-and-mouth disease virus (FMDV) initiates infection by adhering to integrin receptors on target cells, followed by cell entry and disassembly of the virion through acidification within endosomes. Mild heating of the virions also leads to irreversible dissociation into pentamers, a characteristic linked to reduced vaccine efficacy. In this study, the structural stability of intra- and inter-serotype chimeric SAT2 and SAT3 virus particles to various conditions including low pH, mild temperatures or high ionic strength, was compared. Our results demonstrated that while both the SAT2 and SAT3 infectious capsids displayed different sensitivities in a series of low pH buffers, their stability profiles were comparable at high temperatures or high ionic strength conditions. Recombinant vSAT2 and intra-serotype chimeric viruses were used to map the amino acid differences in the capsid proteins of viruses with disparate low pH stabilities. Four His residues at the inter-pentamer interface were identified that change protonation states at pH 6.0. Of these, the H145 of VP3 appears to be involved in interactions with A141 in VP3 and K63 in VP2, and may be involved in orientating H142 of VP3 for interaction at the inter-pentamer interfaces.